Credit-Investment Activity of Banks of the Ukraine: Financial Globalization, Risks, Stabilization - Trusova, Natalia; Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Melnyk, L.; Shіlo, Z.; Prystеmskyi, O. (My University, 2021)
Today the problem of managing credit and investment risk in the bank in the context of financial globalization remains one of the most relevant problems. At the same time, science may not yet explain the answers to some questions and the banker needs to solve them in practice. Therefore, the construction of a comprehensive system of credit and investment risk management in banks is one of the main components of security effective lending activities of banks. The article considers the features of credit and investment activities of banks in the interbank market in the context of financial globalization. The article reveals that the main economic function of Ukrainian banks in the period of accession to the EU is the credit and investment activity of their clients. State of the loan and investment portfolio and dynamics of loans were analyzed. The model and methods of the integrated stabilizer of credit and investment activity of the bank on the interbank market are developed. The authors proposed a list of methods and actions that unify threats, identify risks and improve the credit and innovation activities of the bank in the period of globalization for countries that are in the process of forming the banking infrastructure.
Keywords: loans; deposits; banks; banking system; credit and investment activity; nhreats; risks